Molecular puzzle of insulin: structural assembly pathways and their role in diabetes - Urbaniak, Edyta; Henry, Sara; Lalowski, Maciej; Borowiak, Malgorzata (Frontiers in Cell and Developmental Biology, 2025)
Properly folded proteins are essential for virtually all cellular processes including enzyme catalysis, signal transduction, and structural support. The cells have evolved intricate mechanisms of control, such as the assistance of chaperones and proteostasis networks, to ensure that proteins mature and fold correctly and maintain their functional conformations. Here, we review the mechanisms governing the folding of key hormonal regulators or glucose homeostasis. The insulin synthesis in pancreatic β-cells begins with preproinsulin production. During translation, the insulin precursor involves components of the endoplasmic reticulum (ER) translocation machinery, which are essential for proper orientation, translocation, and cleavage of the signal peptide of preproinsulin. These steps are critical to initiate the correct folding of proinsulin. Proinsulin foldability is optimized in the ER, an environment evolved to support the folding process and the formation of disulfide bonds while minimizing misfolding. This environment is intricately linked to ER stress response pathways, which have both beneficial and potentially harmful effects on pancreatic β-cells. Proinsulin misfolding can result from excessive biosynthetic ER load, proinsulin gene mutations, or genetic predispositions affecting the ER folding environment. Misfolded proinsulin leads to deficient insulin production and contributes to diabetes pathogenesis. Understanding the mechanisms of protein folding is critical for addressing diabetes and other protein misfolding-related diseases.